Analisis Karangan Cerita Pendek Siswa Kelas IV SDN Cilincing 05 Kota Jakarta Utara pada Pembelajaran Bahasa Indonesia - Eugenia, Anastasya; Widjojoko, Widjojoko; Wardana, Deni (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Understanding the structure of a short story composition is very important for elementary school students. Through this structure, it will greatly help students in the future in world education because the structure of an essay will bring students to understanding written work. So far, students in making short story essays have ignored the intrinsic elements, it is very unfortunate if there are ideas to make essays but they are not arranged systematically. Through the learning material to make short stories, it is hoped that students can always pour their thoughts into a written work, but in fact, students can understand the material that is currently obtained because of the current learning system through long distances. This research is here to analyze the short story essays of the fourth-grade students of SDN Cilincing 05, North Jakarta City. This research will focus on the intrinsic elements contained in students' short story essays, including the theme, the plot of the place, the timeline, and the mandate contained in the short story essay written by students. Then the data goes through the data reduction process, traffic is in the form of tables in order to make it easier for understanding in understanding the content of the research. The data that has been obtained is then analyzed by researchers using content analysis research methods. Content analysis is certainly the right method for this research because content analysis reveals the meaning of a text. From the research that has been done, teaching materials are obtained to write short stories by paying attention to the intrinsic elements to make it easier for students to make essays